2020
DOI: 10.1167/iovs.61.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Electrical Stimulation Improves Photoreceptor Survival and Retinal Function in Mice with Inherited Photoreceptor Degeneration

Abstract: PURPOSE. Neurons carry electrical signals and communicate via electrical activities. The therapeutic potential of electrical stimulation (ES) for the nervous system, including the retina, through improvement of cell survival and function has been noted. Here we investigated the neuroprotective and regenerative potential of ES in a mouse model of inherited retinal degeneration. METHODS. Rhodopsin-deficient (Rho −/−) mice received one or two sessions of transpalpebral ES or sham treatments for 7 consecutive days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…To assess the direct impact of the electrical field on microglial function, we investigated the cell motility following ES in cultured BV-2 cells, a murine microglial cell line, using the scratch assay. Our previous studies suggest that while neurons and glial cells respond robustly to electrical microcurrents (100 μA; 20 Hz) ( Enayati et al, 2020 ; Yu et al, 2020 ), the ramp waveform evokes the most prominent result in glial cells compared to the other waveforms. We compared BV-2’s responses to three different ES waveforms ramp ( Figure 1A ), rectangular ( Figure 1B ), and sine ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the direct impact of the electrical field on microglial function, we investigated the cell motility following ES in cultured BV-2 cells, a murine microglial cell line, using the scratch assay. Our previous studies suggest that while neurons and glial cells respond robustly to electrical microcurrents (100 μA; 20 Hz) ( Enayati et al, 2020 ; Yu et al, 2020 ), the ramp waveform evokes the most prominent result in glial cells compared to the other waveforms. We compared BV-2’s responses to three different ES waveforms ramp ( Figure 1A ), rectangular ( Figure 1B ), and sine ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…In excitable cells such as cochlear neurons, the ramp waveform is reported to require less voltage than the rectangular waveform to evoke auditory brainstem response, suggesting that the ramp waveform is more efficient in generating electrical field in tissues ( Navntoft et al, 2020 ). Our previous reports showed that the ramp waveform is also more efficient in evoking a regenerative response of Müller cells, likely making it a preferable form of ES with optimal neuroprotective effects in the eye through mediating multiple cell types ( Enayati et al, 2020 ; Yu et al, 2020 ). Furthermore, as ramp ES exerts its effect at a low current and voltage, this may also reduce the risk of complications in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, electrical stimulation exerted a neuroprotective effect on RGCs, followed by the development of a transcorneal electrical stimulation (TcES) device that could be used in humans 4. Animal models of retinitis pigmentosa (RP), including rats and rabbits,5–7 and clinical studies on patients with RP mentioned that TcES can protect retinal photoreceptors. Moreover, TcES improves the visual acuity, visual fields and electroretinograms 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation (ES) has been suggested to affect neural stem cell fate and function in vivo [3]. Our recent study reported potential reprogramming responses of MCs following ES in a mouse model of inherited photoreceptor degeneration [4]. In line with this observation, many years ago Chow and team accidently discovered that low electric current could reverse the visual field and function loss in a safety assessment of an artificial silicon retina microchip in retinitis pigmentosa (RP) patients, in which the effect was observed far from the initial stimulation point [5].…”
Section: Introductionmentioning
confidence: 99%